2005
DOI: 10.1002/chin.200518167
|View full text |Cite
|
Sign up to set email alerts
|

A New ent‐Kaurane Diterpenoid from Isodon excisoides (Sun ex C. H. Hu) C. Y. Wu et H. W. Li

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
172
0
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(189 citation statements)
references
References 1 publication
3
172
0
14
Order By: Relevance
“…A minimal amount of ammonia was then necessary to obtain a complete coating of particles and a good dispersion of core-shell particles. Nevertheless, a larger amount of ammonia led to the formation of maghemite free silica particles as a result of rapid hydrolysis of TEOS [20]. An ammonia concentration of 0.12 mol/L appeared to be a good compromise.…”
Section: Non-functionalized Core-shell Nanoparticlesmentioning
confidence: 82%
See 1 more Smart Citation
“…A minimal amount of ammonia was then necessary to obtain a complete coating of particles and a good dispersion of core-shell particles. Nevertheless, a larger amount of ammonia led to the formation of maghemite free silica particles as a result of rapid hydrolysis of TEOS [20]. An ammonia concentration of 0.12 mol/L appeared to be a good compromise.…”
Section: Non-functionalized Core-shell Nanoparticlesmentioning
confidence: 82%
“…Silica shell was formed by the condensation of tetraethoxysilane (TEOS) compound in a mixture of ethanol and water [20]. The presence of citrate allows increasing organosilane affinity for particle surface.…”
Section: Non-functionalized Core-shell Nanoparticlesmentioning
confidence: 99%
“…Especially, 2D patterns of tin oxide nano-structures on flexible polymer films are required for light-weight flexible sensors and solar cells. 2D patterning of nanomaterials 119,120 such as metal oxides 33,54,63,75,121,122 , Au clusters 123 , Pt nanoparticles 124 , organic monolayers 125 , bio molecular layers 126 , DNA 127 , etc. is expected to lead to a large step forward in materials science research and the development of new devices.…”
Section: 9mentioning
confidence: 99%
“…26,27 During the REPSM process, switching back to the normal polarity at the right moment is very important, because any back-flush during the stacking period may cause the loss of analytes. [26][27][28] Ding et al revealed that injecting a small plug of buffer after the sample could be used to avoid the possibility of losing any analytes. 28 Therefore, I investigated whether the introduction of a buffer plug after injecting the samples would affect the on-line concentration and separation of the Au NP samples.…”
Section: Effect Of Introducing a Buffer Plug After Injecting The Au Nmentioning
confidence: 99%
“…[26][27][28] Ding et al revealed that injecting a small plug of buffer after the sample could be used to avoid the possibility of losing any analytes. 28 Therefore, I investigated whether the introduction of a buffer plug after injecting the samples would affect the on-line concentration and separation of the Au NP samples.…”
Section: Effect Of Introducing a Buffer Plug After Injecting The Au Nmentioning
confidence: 99%